Peran Penghulu Dalam Meningkatkan Kualitas Pelayanan Administrasi Nikah/Rujuk Pada Kantor Urusan Agama Kecamatan Kota Utara Kota Gorontalo - Umar, Hasan (CV. Dalle’ Deceng Abeeayla, 2024)
This research aims to determine the role of the celebrant in improving the quality of marriage/reconciliation administration services. Apart from that, this research also wants to know what factors hinder the role of the celebrant in improving the quality of marriage/reconciliation administration services at the Religious Affairs Office in the North City District of Gorontalo City. The method used in this research is a qualitative approach. This method attempts to describe or describe in detail or depth by exploring information from the interview process. Based on the results of the research and discussions that have been carried out, it can be concluded that there are still many headmen who have not been able to carry out all the details of these activities well. Apart from that, there are still headmen who do not have a good grasp of the jurisprudence of munakahat and when they are asked for a legal fatwa, they are unable to take legal istinbat. So the leadership must select and assign tasks to the headmaster in accordance with the headman's proportions and profession, so that all the main tasks and details of his activities can be mastered and carried out well. It will also be directed to policy makers to ensure that future candidates for functional leaders truly have adequate basic competencies for a leader.